On Verb Forms with Emphatic Vowels in Megrelian (according to Gali Speech) - Dadiani, Eka (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2022)
In Megrelian emphatic vowels that extend word forms are widespread. Vowels y, u, and ŭ can be attached to words ending in a consonant, including verb forms and perform such functions. In the presented article, the cases of the occurrence of the extending vowel with the verb forms are discussed in the Samurzakano Megrelian, one of the municipalities of currently occupied Abkhazia - according to the Gali speech. The published Megrelian texts (I. Kipshidze 1914; M. Khubua 1938) were taken for analysis, which was compared with the new material recorded in the villages of Gali municipality (Otobaia, Ghumurishi). From the analyzed material, it can be seen that in Samurzako Megrelian, the verb extension vowel is found in a sufficient number, although it is not characterized by such a frequency as it is in Senaki speech. Marker suffixes of person and number can be complicated with a long vowel; The structure of the verb stem (the number of syllables) does not matter, it will be attached to different screeve forms. It occurs with a pause both at the end of a sentence and within it. In a certain position, the unextended variant alternates with the extended form, and in some cases (before the particle -a of reported speech) only the extended option is used. Of the extended vowels, the շ vowel is often used. The occurrence of extended /u/ seems to be due to the phonetic factor: it is mainly found with forms containing a vowel. As a matter of fact, the vowel /i/ is rarely attested in Samurzakano Megrelian. In general, Maghrelian differs from literal Georgian in terms of the frequency of extended verb forms, although similar facts are more or less confirmed in dialects.